The Role of Character Education in Building Morals in Elementary School Students - Lutf, St fanhi Ratu; Nurillahi, Rania Naswa; Arsyih, Azmy; Annisa, Nur; Sardi, st Nurkhalisa; Azhani, Dina Fakhriah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
One of the problems that occurs in the world of education today is the lack of good manners among students. Many students are smart and successful, but lack good manners. The personality of students is manifested in noble morals that will lead the students to great dignity and honor. Therefore, the position of manners in education is very necessary to be applied, it can even be said that it is mandatory for the school to prioritize manners before knowledge. Currently, noble manners are expensive and difficult to find. This study focuses on education in manners in forming students' morals. The purpose of this study is to apply knowing manners in students so that noble morals are formed. This research method uses qualitative to raise facts, circumstances, variables, and phenomena that occur. This type of research is phenomenology. Data collection techniques are observation, interviews and documentation. Data analysis techniques include three qualitative data analysis techniques, namely data condensation, data presentation and drawing conclusions. The results of this study found that strengthening manners in students is urgently needed in order to form noble morals. This moral education is carried out through habituation, and the process of implementing moral education includes various activities with the term ta'dib, morals applied by students.